Law enforcement - Cassedy, Patrice (San Diego, Calif. : Lucent Books, 2002)
Provides an overview of careers in the various fields of law enforcement, including educational requirements, salaries, necessary personality traits, job descriptions, and the dangers inherent in some positions.
Federal agents -- Correctional officers -- Police officers and detectives -- Criminalists and crime scene technicians -- Probation and parole officers.
10 years and up
Keywords: Law enforcement -- Vocational guidance -- United States; Law enforcement -- Vocational guidance; Vocational guidance